2016
DOI: 10.1515/jce-2016-0028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Coronary Plaque Vulnerability in Acute Coronary Syndromes using Optical Coherence Tomography and Intravascular Ultrasound. A Systematic Review

Abstract: The aim of this systematic review was to analyze studies characterizing vulnerable coronary plaques using optical coherence tomography (OCT) and intravascular ultrasound (IVUS), in order to identify the most efficient invasive technique permitting plaque characterization in patients with acute myocardial infarction. Method: A total number of 432 studies were identified, 420 through database searching and 12 through manual searching. Eight duplicate studies were removed, leaving a total number of 424 studies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…[59][60][61] Two of the largest EAT studies included cohorts of patients with no cardiovascular disease. The MESA trial/ study showed a positive association between the coronary artery calcium score and the EFV assessed by CT, but the Heinz-Nixdorf Recall study found that EAT predicted an excessive risk for coronary events, independently of the calcium score and classic cardiovascular risk factors.…”
Section: 50-52mentioning
confidence: 99%
“…[59][60][61] Two of the largest EAT studies included cohorts of patients with no cardiovascular disease. The MESA trial/ study showed a positive association between the coronary artery calcium score and the EFV assessed by CT, but the Heinz-Nixdorf Recall study found that EAT predicted an excessive risk for coronary events, independently of the calcium score and classic cardiovascular risk factors.…”
Section: 50-52mentioning
confidence: 99%
“…[4][5][6][7] Invasive imaging techniques used for the identification of vulnerability markers (VM) for coronary atherosclerosis include intravascular ultrasound (with description of plaque burden, remodeling index, cross sectional area, and necrotic core,), and optical coherence tomography (which measures the thickness of the fibrous arch, lipid arch, intracoronary thrombi, or macrophages). 8,9 Computed tomography coronary angiography (CTCA) is a noninvasive method that provides visualization of the entire coronary tree, as well as the vessel lumen and wall characteristics, while offering similar accuracy in detecting coronary vulnerability as the intracoronary imaging techniques. [10][11][12] VM for coronary plaques assessed via CTCA include the presence and size of the lipid necrotic core, low attenuation plaques (LAP, density of <30 Hounsfield units), positive vessel remodeling (PR), the napkin ring sign (NRS) and spotty calcifications (SC).…”
Section: Vulnerable Coronary Plaquesmentioning
confidence: 99%
“…While computed tomographic angiography (CTA) imaging has a definite role in visualization of several vulnerability features such as positive remodeling, napkin ring sign, spotty calcifications or very low density plaques appearing as dark spots on CTA images, its value remains low in assessing the thickness of the fibrous cap, mainly due to the insufficient resolution [3]. Intravascular imaging techniques, namely intravascular ultrasound (IVUS) and optical coherence tomography (OCT) have been proposed to represent efficient alternatives to CTA imaging for detecting thin cap fibroatheroma as well as for quantification of plaque components [4].…”
Section: Introductionmentioning
confidence: 99%